Management of Septic Shock - Afidatul Umroh (Jurnal Penelitian Perawat Profesional, 2020)
Sepsis is an emergency condition where response of systemic immunity toward infectious pocess may cause fatal organ dysfunction and death. Septic shock is the worst complication of sepsis where hypotension occurs persistently or refractory despite adequate fluid resuscitation. The aim of this literature review is to explain about proper management of septic shock. References which are used in this writing are 34 articles which are collected from PubMed NCBI by doing literature searching and 2 book which are all published in range of year 1994-2020. The keywords which are used for this literature searching are shock, therapy, epidemiology, and risk factor which are also filtered by year of publication in range of 2010-2020. This literature searching yielded 861 article and 34 of them were chosen. The references which has been collected were analyzed by systematic literature review method which include collecting, evaluation, and development of research which certain focii. The results of literature review shows that early and adequate fluid resuscitation is one of the key for successful treatment for septic shock. Steroid administration is commonly done but the benefit of it remains controversial to be accepted generally. Administration of emphirical antibiotic is reccomended as it shows to lower mortality in some studies. Team work in the management of shock septic is key to properly treat patients.